2011
DOI: 10.1590/s1984-82502011000200022
|View full text |Cite
|
Sign up to set email alerts
|

Invertase, glucose oxidase and catalase for converting sucrose to fructose and gluconic acid through batch and membrane-continuous reactors

Abstract: Conversion of sucrose into fructose and gluconic acid using invertase, glucose oxidase and catalase was studied by discontinuous (sequential or simultaneous addition of the enzymes) and continuous (simultaneous addition of the enzymes in a 100 kDa-ultrafiltration membrane reactor) processes. The following parameters were varied: concentration of enzymes, initial concentration of substrates (sucrose and glucose), pH, temperature and feeding rate (for continuous process). The highest yield of conversion (100%) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 16 publications
(24 reference statements)
2
7
0
Order By: Relevance
“…In different invertase production time duration experiment, the maximum enzyme activity was observed at 30 h (21.0 Units/ml) of incubation. Further increase in the incubation time significantly reduces the invertase activity its shown in Fig:5 Similar observation has been reported previously with pH 3.5-5.0 [35] and optimum temperature 70°C [36] observation also reported.…”
Section: Invertase Assay For Wild and Mutant Yeastsupporting
confidence: 89%
“…In different invertase production time duration experiment, the maximum enzyme activity was observed at 30 h (21.0 Units/ml) of incubation. Further increase in the incubation time significantly reduces the invertase activity its shown in Fig:5 Similar observation has been reported previously with pH 3.5-5.0 [35] and optimum temperature 70°C [36] observation also reported.…”
Section: Invertase Assay For Wild and Mutant Yeastsupporting
confidence: 89%
“…2). Similar pH optimum for soluble invertase was previously reported (35). Slight shift in pH optimum of soluble invertase and invertase immobilized on insoluble carriers is a common phenomenon described in previous research papers (9,36,37).…”
Section: Determination Of Optimum Ph and Ph Stabilitysupporting
confidence: 86%
“…This enzyme-powered device was successfully employed in Catalysis Science & Technology Mini review the autonomous and on-demand delivery of doxorubicin in HeLa cancer treatment. 307 Some studies reported the use of maltose and sucrose as substrates for D-gluconic acid production in batches using catalase to destroy the hydrogen peroxide 21,308,309 and using fed-batch, 310 continuous 311 and membrane-continuous 309,310 processes. In general, all processes were satisfactory, reaching high yields of conversion of maltose and sucrose to D-gluconic acid.…”
Section: Conversion Of Disaccharides To D-gluconic Acidmentioning
confidence: 99%